2016
DOI: 10.20286/nova-jmbs-050203
|View full text |Cite
|
Sign up to set email alerts
|

A study of lipid profile Levels of Type II Diabetes Mellitus

Abstract: This study consists of two parts; the Part one is to evaluate the level of Blood glucose and lipid profile among diabetic patients(121 patients) which are compared with non-diabetic subjects (60 persons) and part two is to correlate lipid profile with cardiovascular abnormalities among type II diabetic patients. The diabetic patients were collected from Jabir Aboeleiz Center for Diabetes (51.9±11.22 years). Sixty healthy non-diabetic subjects were chosen as controls (52.44±10.76years). Blood glucose, total cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
3
4
0
Order By: Relevance
“…value of healthy control category (P=0.000). This finding was supported by a previous study [26] that found that the mean fasting glucose level of type II diabetic patients was significantly higher (p=0.001) than that of non-diabetic subjects [26]. The mean of glucose for the hypertension group was not significantly different from the control healthy group (P=0.942), which is consistent with [27] that found no statistically significant correlation between systolic blood pressure and fasting plasma glucose, but significant correlation between fasting plasma glucose and diastolic blood pressure [27].…”
Section: Resultssupporting
confidence: 92%
“…value of healthy control category (P=0.000). This finding was supported by a previous study [26] that found that the mean fasting glucose level of type II diabetic patients was significantly higher (p=0.001) than that of non-diabetic subjects [26]. The mean of glucose for the hypertension group was not significantly different from the control healthy group (P=0.942), which is consistent with [27] that found no statistically significant correlation between systolic blood pressure and fasting plasma glucose, but significant correlation between fasting plasma glucose and diastolic blood pressure [27].…”
Section: Resultssupporting
confidence: 92%
“…In our research findings in human serum, the lipid profile tests (Cholesterol, triglyceride, LDL and VLDL) had abnormal values among studied groups, while HDL was non-significant in the mentioned groups. In accordance with a Sudanese study, all serum lipids and lipoproteins were considerably greater in diabetic patients than in non-diabetic subjects, with the exception of HLD, which was significantly lower in diabetic patients than in non-diabetic people (28) . In diabetic males and females of both age groups, however, serum TC, LDL-C, and TG levels were statistically considerably higher, but HDL-C levels were dramatically lowered (29).…”
Section: Discussionsupporting
confidence: 89%
“…Reduce peripheral insulin sensitivity with increased hepatic glucose output resulting in the development of hyperglycemia (König & Holzhütter 2012). Additionally, high levels of circulating fatty acids due to promotion of lipolysis, elevated levels of triglycerides, cholesterol and LDL-C with low levels of HDL-C were recognized in type 2 diabetic patients (Abd El-Azim et al 2013; Sabahelkhier et al 2016). The chronic hyperglycemia of diabetes is associated with longterm damage, dysfunction, and failure of different organs, especially the eyes, kidneys, nerves, heart, and blood vessels.…”
Section: Introductionmentioning
confidence: 99%